Measuring the variability of personality traits with interval responses: Psychometric properties of the dual-range slider response format - Kloft, Matthias; Snijder, Jean-Paul; Heck, Daniel W. (Behavior research methods, 2024)
Measuring the variability in persons’ behaviors and experiences using ecological momentary assessment is time-consuming and costly. We investigate whether interval responses provided through a dual-range slider (DRS) response format can be used as a simple and efficient alternative: Respondents indicate variability in their behavior in a retrospective rating by choosing a lower and an upper bound on a continuous, bounded scale. We investigate the psychometric properties of this response format as a prerequisite for further validation. First, we assess the test-retest reliability of factor-score estimates for the width of DRS intervals. Second, we test whether factor-score estimates of the visual analog scale (VAS) and the location of DRS intervals show convergent validity. Third, we investigate whether factor-score estimates for the DRS are uncorrelated between different personality scales. We present a longitudinal multitrait-multimethod study using two personality scales (Extraversion, Conscientiousness) and two response formats (VAS, DRS) at two measurement occasions (6-8 weeks apart) for which we estimate factor-score correlations in a joint item response theory model. The test-retest reliability of the width of DRS intervals was high ($$\hat{ρ } \ge .73$$). Also, convergent validity between location scores of VAS and DRS was high ($$\hat{ρ } \ge .88$$). Conversely, discriminant validity of the width of DRS intervals between Extraversion and Conscientiousness was poor ($$\hat{ρ } \ge .94$$). In conclusion, the DRS seems to be a reliable response format that could be used to measure the central tendency of a trait equivalently to the VAS. However, it might not be well suited for measuring intra-individual variability in personality traits.
Gesehen am 26.07.2024